Adhesion mechanism of different alkyltrichlorosilanes enhanced superhydrophobicity on superhydrophilic sio2 film prepared by dip coating - Atchara Sriboonruang (2020)
© 2020, Chiang Mai University. All rights reserved. Superhydrophilic silica (SiO2) nanoparticles (NPs) were successfully modified superhydrophobic SiO2 NPs via a facile one-step reaction technique. The modified SiO2 NPs with different alkyltrichlorosilanes (ATCS) were then coated on a glass substrate by dip-coating process. The effect of different ATCS chain lengths such as methyltrichlorosilane (C1), butyltrichlorosilane (C4), and octadecyltrichlorosilane (C18) on superhydrophobicity was investigated. The result showed the particle sizes of modified SiO2 NPs slightly increases with the chain length. Likewise, the water contact angle (WCA) of C1, C4 and C18 modified SiO2 NPs were 156º, 159º and 160º. Furthermore, the sliding angle (SA) of all the modified SiO2 NPs are less than 3º. It is clearly indicated that ATCS with different chain lengths modified SiO2 NPs were superhydrophobic. Interestingly, ATCSs modified SiO2 NPs have high transparency with optical transmittance greater than 80%. This is a key opportunity for self-cleaning applications.